Release of Obstructive Prostatic Disease and Improvement of Erectile Dysfunction by Repetitive Prostatic Massage and Antimicrobial Therapy - Bradley R. Hennenfent; Antonio Novak Feliciano (The Scientific World Journal)
We report on a 69-year-old male who presented with an indwelling urinary catheter due to obstructive prostatic disease. The patient also complained of impotence. With repetitive prostatic massage combined with antimicrobial therapy the urinary obstruction was released, the patient's urinary symptoms resolved, and sexual function improved.